2016
DOI: 10.5194/hess-20-4129-2016
|View full text |Cite
|
Sign up to set email alerts
|

Relative impacts of land use and climate change on summer precipitation in the Netherlands

Abstract: Abstract. The effects of historic and future land use on precipitation in the Netherlands are investigated on 18 summer days with similar meteorological conditions. The days are selected with a circulation type classification and a clustering procedure to obtain a homogenous set of days that is expected to favor land impacts. Changes in precipitation are investigated in relation to the present-day climate and land use, and from the perspective of future climate and land use. To that end, the weather research a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…It resulted in weather condition alterations and climatic extremes. Potential climate change can affect the hydrological cycle largely through changes in spatio-temporal patterns of precipitation [2][3][4], increase of temperatures [5], frequent occurrence of hydrological extremes, such as floods and drought [6], rise of sea level [7], reduction of snow cover and changes in soil moisture [8], etc. Undoubtedly, semi-arid and arid areas of the Mediterranean Basin are among the zones affected by climate change [9].…”
Section: Introductionmentioning
confidence: 99%
“…It resulted in weather condition alterations and climatic extremes. Potential climate change can affect the hydrological cycle largely through changes in spatio-temporal patterns of precipitation [2][3][4], increase of temperatures [5], frequent occurrence of hydrological extremes, such as floods and drought [6], rise of sea level [7], reduction of snow cover and changes in soil moisture [8], etc. Undoubtedly, semi-arid and arid areas of the Mediterranean Basin are among the zones affected by climate change [9].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the impact of anthropogenic aerosols on the decrease in precipitation was remarkable in summer and was possibly caused by the influence of aerosols on convective precipitation in North China [50]. Daniels et al [49] used a regional climate model to simulate the effect of land use changes on precipitation in the Netherlands, and found that the simulated effects of land use changes on precipitation in summer are smaller than the effects of climate change, but are not negligible. Thus, it is difficult to directly compare the variations in precipitation indices in the MRB to other studies.…”
Section: Attribution Analysismentioning
confidence: 99%
“…Domains 2-4 zoom in on the Rijnmond area in the southwest of the Netherlands. Based on previous studies over the Netherlands (Bozhinova et al, 2014;Daniels et al, 2016;Steeneveld et al, 2014), we have used the Yonsei University (YSU) boundary layer scheme (Hong et al, 2006), the Dudhia scheme for shortwave radiation (Dudhia, 1989), the Rapid Radiation Transfer Model (RRTM) as the longwave radiation scheme (Mlawer et al, 1997) and the Unified Noah Land-Surface Model as the surface physics scheme (Ek et al, 2003). We also used the single-layer urban canopy model (UCM) to account for changes in roughness length and heat fluxes in the urban environment , although the impact of the UCM model on simulated mixing ratios is very small in our domain.…”
Section: Eulerian Modelmentioning
confidence: 99%